ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN DI HOTEL PANGERAN BEACH PADANG - Emely, Bamy; Chair, Ira Meirina; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to determine the factors that affect employee job satisfaction, which is seen from the factor of salary, job factors, colleagues factors, employer factors, promotion factors positions and work environment factors. This research is quantitative descriptive with causal associative method. The population is employees at Pangeran Beach Hotel Padang, it is about 162 peoples. Sampling technique is non probability sampling with purposive sampling. The number of data sampel consist of 80 peoples. Data collection techniques using questionnaires with Likert scale. Further data are tested using multiple linear regression which has passed the classical assumption test.The value of coefficient of determination Adjusted R Square 0,909 means the effect of variable X to Y of 90.9%. So, the conclution of variable factors of salary, job factors, employer, promotion factors positions and work environment factors have significant effect on employee job satisfaction, because the significant valve <0,05. While the variable factor of colleagues do not have significant effect, because the valve >0,05.Keywords: factor of salary, job factors, colleagues factors, employer factors, promotion factors positions, work environment factors , job satisfaction.